The features of syntax Cophys in Motanabbi poetry - عبد الله محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
In research summary ,I follow apartical study in which I clarified the applied features of the syntax of on a poet of a poet months ago the arab ports, are a Motanabbi, and is a great benefit because it is the way to show us the user and the unemployed, one controversial issue is that theoretical grammar that remains in the books and is not written on the rich of poets literary and eloquent writers will be forgotten and neglected. The research began with an introduction showing its importance, reason for its selection, purpose and methodologs. After that prepared to talks about the research theme by talking by talking about the grammatical Motanabbi the arab scholar . The views that prose represents in his poet are being presented in the eccical doctrine . This is based on the limited page research requirements and on the book (equity in issues ) , the different grammar or other grievances mentioned the grammar provision. And the verse that represent debating and testing, a final discussion is the most important findings of the research .